The making and unmaking of the English Catholic intellectual community, 1910 - 1950 - Lothian, James R. (Univ. of Notre Dame Press, 2009)
Prologue -- From political radicalism to political Catholicism : Hilaire Belloc and the roots of the English Catholic intellectual community -- The greater servants : McNabb, Gill, Chesterton, and the establishment of the Bellocian orthodoxy -- The lesser servants : the next generation and the maturation of the Bellocian orthodoxy -- The Dawsonite challenge -- The unmaking of the English Catholic intellectual community -- Epilogue